CHARACTERISTICS OF RICE HUSK SILICA GRAFTED 4-VINYL PYRIDINE - Irwan Ginting Suka; Wasinton Simanjuntak (Universitas Gadjah Mada, 2008)
This study was carried out to investigate the grafting of4-Vinyl Pyridine (4-VP) on silica prepared from rice husk, with the main aim to study wether the 4-VP grafted retains its characteristics. For this purpose, the grafted silica was analysed using FTIR spectroscopic method, followed by testing of the sample for solvent adsorption, Cu2+ adsorption from solution, and bacterial inhibitions, since 4-VP has been known to possess such properties. The FTIR analysis revealed that under the experimental conditions applied, the 4-PV was well grafted onto silica surface. The success of grafting was also supported by the results of solvent adsorption, which indicate the increase in adsorption capacity with increased percent of grafting and higher adsorption capacity toward polar solvent. The same supports are also provided by the ability of the sample to adsorp results of Cu2+ adsorption from solution, and the ability of the sample to inhibit the microorganism growth.